2020
DOI: 10.3390/agronomy10121912
|View full text |Cite
|
Sign up to set email alerts
|

Orchard Planting Density and Tree Development Stage Affects Physiological Processes of Apple (Malus domestica Borkh.) Tree

Abstract: One of the most important factors affecting photosynthesis and metabolism is light absorbance by leaves and penetration through the canopy. The aim of this study was to evaluate the influence of planting density and tree development stages on photosynthetic activity, photosynthetic pigments, and carbohydrates in apple (Malus domestica Borkh.) trees in a combined way. The apple tree, Auksis, was grafted on dwarfing rootstock P 22. Space between rows was 3 m, trees were planted in 2001 in four distances: 0.25 m,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…Previous data showed that increased cv. Auksis tree density negatively affected photosynthesis intensity and other indices related with photosynthetic response [ 7 , 8 ]. The carbohydrates produced in the leaves are further transported to the fruit, so the amount of carbohydrates in the fruit strongly depends on the production in the leaves [ 13 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous data showed that increased cv. Auksis tree density negatively affected photosynthesis intensity and other indices related with photosynthetic response [ 7 , 8 ]. The carbohydrates produced in the leaves are further transported to the fruit, so the amount of carbohydrates in the fruit strongly depends on the production in the leaves [ 13 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study confirmed that the planting density did not have a significant effect on the accumulation of sugars in the leaves of the apple tree cv. Auksis [ 8 ], and neither on the amount of sugars in the fruit ( Table 1 ). P 60 dwarfing rootstock and P 22 super dwarfing rootstock had different effects on carbohydrate content in fruits; significant differences were found for sorbitol and starch content ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Robinson et al (2013) suggested that the optimum planting density is approximately 2700 trees/ha, although super spindle orchards can be larger than 5450 trees/ha. Recent studies have examined densities as high as 13,000 trees/ha (Lauzike et al 2020), although more moderate estimations found peak productivity to be approximately 4762 trees/ha (Leão de Sousa and Gonc ¸alves 2022).…”
mentioning
confidence: 99%